Land Surveying, Local Government, Sustainable Development & Construction Industry. A Brief Reviews On Their Connectivity - Sulzakimin Mohamed (Penerbit UTHM, 2023)
Land surveying is an art and sciences that cannot be denied its contribution in the planning and development of any constructions project. It can lead to changes not only to human life but also to the surrounding environment since it deals with the exploration of new land or re using the old one. The intention of this book is to acquaint with the land surveying, local government, sustainable development and construction industry. Objectively, it is to make some connection from land surveying, local government, sustainable development and construction industry. Furthermore, it is to make sense the modernisation it can bring and move towards better living to all. This book is an effort to discuss and review on the relationship and connectivity of land surveying, local government, sustainable development and construction industry. This book materialised due to the realization that there is lack of books that revolve and connect land surveying, local government, sustainable development and construction industry. This book targeted at students majoring in construction management in institutions of higher learning in Malaysia. It is expected to be able to meet the needs for future generations and it is expected to have a positive impact on the community of academia and practitioners.